Gamma Distribution, - Distribution, Student T-Distribution, Fisher F - Distribution
Gamma Distribution, - Distribution, Student T-Distribution, Fisher F - Distribution
Gamma Distribution, - Distribution, Student T-Distribution, Fisher F - Distribution
Student t-distribution,
Fisher F -distribution.
Gamma distribution. Let us take two parameters > 0 and > 0. Gamma function () is dened by () = x1 ex dx.
0
where we made a change of variables x = y. Therefore, if we dene 1 x x e , x0 () f (x|, ) = 0, x<0 then f (x|, ) will be a probability density function since it is nonnegative and it integrates to one. Denition. The distribution with p.d.f. f (x|, ) is called Gamma distribution with parameters and and it is denoted as (, ). Next, let us recall some properties of gamma function (). If we take > 1 then using integration by parts we can write: 1 x () = x e dx = x1 d(ex ) 0 0 = x1 (ex ) (ex )( 1)x2 dx 0 0 = ( 1) x(1)1 ex dx = ( 1)( 1).
0
35
ex dx = 1
(2) = 1 1, (3) = 2 1, (4) = 3 2 1, (5) = 4 3 2 1 and proceeding by induction we get that (n) = (n 1)! Let us compute the kth moment of gamma distribution. We have, k k 1 x EX = x x e dx = x(+k)1 ex dx () () 0 0 ( + k) +k = x+k1 ex dx () +k ( + k) 0 p.d.f. of ( + k, ) integrates to 1 ( + k) ( + k) ( + k 1)( + k 1) = = = +k k () () () k ( + k 1)( + k 2) . . . () ( + k 1) = = . k () k Therefore, the mean is EX = the second moment is EX 2 = and the variance ( + 1) 2 Var(X) = EX (EX) = = 2. 2
2 2
( + 1) 2
Below we will need the following property of Gamma distribution. Lemma. If we have a sequence of independent random variables X1 (1 , ), . . . , Xn (n , ) then X1 + . . . + Xn has distribution (1 + . . . + n , )
Proof. If X (, ) then a moment generating function (m.g.f.) of X is
tX tx 1 x Ee = e x e dx = x1 e(t)x dx () () 0 0 ( t) 1 (t)x = x e dx . ( t) 0 () 36
The function in the last (underbraced) integral is a p.d.f. of gamma distribution (, t) and, therefore, it integrates to 1. We get, tX Ee = . t Moment generating function of the sum n Xi is i=1 Ee
t Pn
i=1
Xi
=E
n i=1
tXi
n i=1
Ee
tXi
n i P i = = t t i=1
Xi
n i=1
i , .
2 -distribution. In the previous lecture we dened a 2 -distribution with n degrees n n 2 2 of freedom as a distribution of the sum X1 + . . . + Xn , where Xi s are i.i.d. standard normal. We will now show that which 2 -distribution coincides with a gamma distribution ( n , 1 ), n 2 2 i.e. n 1 2 = , . n 2 2 Consider a standard normal random variable X N(0, 1). Let us compute the distribution of X 2 . The c.d.f. of X 2 is given by x t2 1 2 P(X x) = P( x X x) = e 2 dt. 2 x
d The p.d.f. can be computed by taking a derivative dx P(X x) and as a result the p.d.f. of X 2 is x ( x)2 ( x)2 t2 d 1 1 1 e 2 dt = e 2 ( x) e 2 ( x) fX 2 (x) = dx x 2 2 2 1 1 x 1 1 1 x = e 2 = x2 e 2 . 2 x 2
We see that this is p.d.f. of Gamma Distribution ( 1 , 1 ), i.e. we proved that X 2 ( 1 , 1 ). 2 2 2 2 2 2 Using Lemma above proves that X1 + . . . + Xn ( n , 1 ). 2 2 Fisher F -distribution. Let us consider two independent random variables, k 1 m 1 2 2 X k = , and Y m = , . 2 2 2 2 Denition: Distribution of the random variable Z= X/k Y /m
37
is called a Fisher distribution with degrees of freedom k and m, is denoted by F k,m . 2 2 First of all, let us notice that since X 2 can be represented as X1 + . . . + Xk for i.i.d. k standard normal X1 , . . . , Xk , by law of large numbers, 1 2 2 2 (X + . . . + Xk ) EX1 = 1 k 1 when k . This means that when k is large, the numerator X/k will concentrate near 1. Similarly, when m gets large, the denominator Y /m will concentrate near 1. This means that when both k and m get large, the distribution Fk,m will concentrate near 1. Another property that is sometimes useful when using the tables of F -distribution is that 1 Fk,m (c, ) = Fm,k 0, . c This is because X/k Y /m 1 1 Fk,m (c, ) = P c =P = Fm,k 0, . Y /m X/k c c Next we will compute the p.d.f. of Z Fk,m . Let us rst compute the p.d.f. of k X Z= . m Y The p.d.f. of X and Y are
1 ( 1 )
2 k 1 1 x ( 2 )
2 m 1 1 y 2 2 2 f (x) =
k x
e and g(y) =
m y
2 e 2 ( 2 ) ( 2 )
k m
correspondingly, where x 0 and y 0. To nd the p.d.f of the ratio X/Y, let us rst write its c.d.f. Since X and Y are always positive, their ratio is also positive and, therefore, for t 0 we can write: ty X P t = P(X tY ) = f (x)g(y)dx dy Y 0 0
since f (x)g(y) is the joint density of X, Y. Since we integrate over the set {x ty} the limits of integration for x vary from 0 to ty. Since p.d.f. is the derivative of c.d.f., the p.d.f. of the ratio X/Y can be computed as follows: d X d ty P t = f (x)g(y)dxdy = f (ty)g(y)ydy dt Y dt 0 0 0 1 k 1 m 2 ( 2 )
2 k m 1 1 ty ( 2 )
1 1 y 2 (ty)
2 e 2 =
e 2 ydy m y
k ( 2 ) ( 2 )
0 1 k+m (2) 2 k 1 1 ( k+m t
2 y
2 )1 e 2 (t+1)y dy =
k m ( 2 )( 2 ) 0 38
The function in the underbraced integral almost looks like a p.d.f. of gamma distribution (, ) with parameters = (k + m)/2 and = 1/2, only the constant in front is missing. If we miltiply and divide by this constant, we will get that, k+m k+m 1 (1) 2 ( k+m ) ( 2 (t + 1)) 2 ( k+m )1 1 (t+1)y k d X 1 2 2 P t = t2 y 2 e 2 dy k+m dt Y ( k )( m ) ( k+m ) ( 1 (t + 1)) 2 0 2 2 2 2 = ( k+m ) k 1 k+m 2 t 2 (1 + t) 2 , k m ( 2 )( 2 )
since the p.d.f. integrates to 1. To summarize, we proved that the p.d.f. of (k/m)Z = X/Y is given by ( k+m ) k k+m fX/Y (t) = k 2 m t 2 1 (1 + t) 2 . ( 2 )( 2 ) Since kt k kt = fZ (t) = P(Z t) = fX/Y , Y m t m m this proves that the p.d.f. of Fk,m -distribution is P(Z t) = P fk,m (t) = = ( k+m ) k kt k 1 kt k+m 2 2 2 1+ . k m m m m ( 2 )( 2 ) X
if X1 , Y1 , . . . , Yn are i.i.d. standard normal. Let us compute the p.d.f. of T. First, we can write, 2 X1 P(t T t) = P(T 2 t2 ) = P t2 . 2 (Y12 + + Yn )/n If fT (x) denotes the p.d.f. of T then the left hand side can be written as t P(t T t) = fT (x)dx.
t 2 X1 2 (Y12 + . . . + Yn )/n
Student tn -distribution. Let us recall that we dened tn -distibution as the distribution of a random variable X1 T = 1 2 (Y12 + + Yn ) n
has Fisher F1,n -distribution and, therefore, the right hand side can be written as t2 f1,n (x)dx.
0
39
We get that,
Taking derivative of both side with respect to t gives fT (t) + fT (t) = f1,n (t2 )2t. But fT (t) = fT (t) since the distribution of T is obviously symmetric, because the numerator X has symmetric distribution N (0, 1). This, nally, proves that fT (t) = f1,n (t2 )t = ( n+1 ) 1 t2 n+1 2 (1 + ) 2 . n ( 1 )( n ) n 2 2
fT (x)dx =
t
t2
f1,n (x)dx.
40